The Role Of Leadership, Organizational Culture, Emotional Intelligence On Employee Loyalty - Novi Novianti; Sri Ayuni; Sunimah Sunimah (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The research aims to evaluate the effect of leadership roles, organizational culture, and emotional intelligence on employee loyalty at PT PGN Solution, Cirebon City, Indonesia. Data was collected from 90 participants through total sampling method by distributing questionnaires. Statistical analysis was conducted using multiple linear regression tests using SPSS version 20 software. The results showed that leadership does not affect employee loyalty, as evidenced by the t-count value of 1.889, below the t-table value of 1.661. Organizational culture positively affects employee loyalty, as evidenced by the t-count value of 3.013, above the t-table value of 1.661. Emotional intelligence positively affects employee loyalty. This is also evidenced by the t-count value of 9.314, above the t-table value of 1.661, and the combination of leadership roles, organizational culture, and emotional intelligence together has a substantial positive effect on employee loyalty, as indicated by the F-count of 194.372, higher than the F-table value of 3.10. This study implies that in the context of PT PGN Solution in Cirebon City, Indonesia, the role of leadership individually does not significantly affect employee loyalty. However, organizational culture and emotional intelligence have a significant positive impact on employee loyalty.